2020
DOI: 10.1101/2020.11.24.20237719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 infection in the craft and manual worker population of Qatar

Abstract: BackgroundQatar experienced a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic that disproportionately affected the craft and manual worker (CMW) population who comprise 60% of the total population. This study aimed to assess the proportions of ever and/or current infection in this population.MethodsA cross-sectional population-based survey was conducted during July 26-September 09, 2020 to assess both anti-SARS-CoV-2 positivity through serological testing and polymerase chain reaction (PC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…Indeed, a nation-wide population-based survey in Qatar showed that 58.5% of those who were PCR positive in this survey reported no symptoms during the last two weeks preceding the survey [ 8 ]. The growing number of serological testing studies in Qatar have also shown that the vast majority of those who are antibody-positive were never diagnosed with this infection [ 8 , 10 , 12 , 24 ]. For instance, out of all those antibody-positive in a nation-wide seroprevalence survey of the CMW population, only 9.3% had a documented, PCR-confirmed infection prior to antibody testing [ 10 ], affirming that as estimated by the model, nine of every 10 infections were never diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, a nation-wide population-based survey in Qatar showed that 58.5% of those who were PCR positive in this survey reported no symptoms during the last two weeks preceding the survey [ 8 ]. The growing number of serological testing studies in Qatar have also shown that the vast majority of those who are antibody-positive were never diagnosed with this infection [ 8 , 10 , 12 , 24 ]. For instance, out of all those antibody-positive in a nation-wide seroprevalence survey of the CMW population, only 9.3% had a documented, PCR-confirmed infection prior to antibody testing [ 10 ], affirming that as estimated by the model, nine of every 10 infections were never diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of serological testing studies in Qatar have also shown that the vast majority of those who are antibody-positive were never diagnosed with this infection [ 8 , 10 , 12 , 24 ]. For instance, out of all those antibody-positive in a nation-wide seroprevalence survey of the CMW population, only 9.3% had a documented, PCR-confirmed infection prior to antibody testing [ 10 ], affirming that as estimated by the model, nine of every 10 infections were never diagnosed. These findings are also consistent with a growing body of serological evidence from other countries [ 32 - 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently assessed the risk and incidence rate of documented reinfection in a cohort of 130,266 SARS-CoV-2 polymerase chain reaction (PCR)-confirmed infected persons in Qatar [5], a country of 2.8 million population [10,11] that experienced a large SARS-CoV-2 epidemic [12][13][14][15][16]. Benefiting from a centralized data-capture system for nationwide SARS-CoV-2 PCR testing and using viral genome sequencing, we quantified the risk of reinfection at ~2 reinfections per 10,000 infected persons [5].…”
Section: Introductionmentioning
confidence: 99%